Primary vs. second primary cT1-T2 oral squamous cell carcinoma: comparing the outcomes - Ramirez-Guanche, Noëmi; Jaeken, Fien; Di Santo, Davide; Nuyts, Sandra; Clement, Paul M.; Laenen, Annousschka; Meulemans, Jeroen; Vander Poorten, Vincent (Frontiers in Surgery, 2025)
Introduction and aimHead and neck cancer (HNC) is the third most common cancer worldwide, with oral squamous cell carcinoma (OSCC) having the highest incidence. Despite early diagnosis in 50% of cases, recurrence and poor survival remain concerns. This study compares survival outcomes between primary and second primary cT1-T2 OSCC.Materials and methodsA single-center historical cohort study included 60 patients treated for cT1-T2 OSCC between 2010 and 2022. Patient demographics, tumor characteristics, and treatment modalities were collected. Treatment followed ESMO guidelines, primarily involving surgery with or without postoperative radiotherapy. Kaplan–Meier analysis and Cox proportional hazards models assessed overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS).ResultsThe 2- and 5-year OS rates were 85% and 64.9%, while DSS rates were 91.4% and 87.3%, respectively. Median OS was 7.4 years. Patients with primary tumors had significantly better OS (HR = 0.409, p = 0.038) and DFS (HR = 0.399, p = 0.036) than those with second primary tumors. Female patients had a 74.7% lower risk of death, and males had significantly shorter DFS (p = 0.024). Advancing tumor stage increased disease-specific mortality risk (HR = 1.737, p = 0.043). Multiple lymph node involvement correlated with worse OS (HR = 2.884, p = 0.031) and DFS (HR = 3.971, p = 0.006). Gross extranodal extension (ENE) was significantly associated with poorer OS (p = 0.048) and showed a borderline association with DFS (p = 0.050).ConclusionThis study confirms second primary malignancies as a key prognostic factor for survival in OSCC. Male sex, advanced TNM stage, gross ENE, multiple lymph node involvement, and active smoking status were linked to poorer outcomes. Larger studies with multivariate analysis comparing primary and non-primary tumors are needed to validate these findings.